Acid Dissociation in (HX)n(H2O)n Clusters (X=F, Cl, Br, I; n=2, 3). Issue 2 (26th October 2022) - Vargas‐Caamal, Alba; Dzib, Eugenia; Ortiz‐Chi, Filiberto; Restrepo, Albeiro; Merino, Gabriel
Abstract: In this work, we analyze the interactions between two or three hydrogen halide molecules and the same number of water moieties through a systematic exploration of their potential energy surfaces. Our results indicate that the most stable HF and HCl aggregates do not experience dissociation of any of the acid fragments, even with three water molecules. In contrast, in the HBr and HI clusters, one of the acid fragments does dissociate. While the global minimum of (HBr)3 (H2 O)3 is a hydrogen‐bridged bihalide anion (BrHBr − ), which is persistent at temperatures up to 203 K, the lowest energy structure of (HI)3 (H2 O)3 has a separated ion pair, but the motif with a bihalide anion (IHI − ) is only 0.2 kcal mol −1 above the global minimum. Among the more stable structures is a broad spectrum of contacts, including water⋯water, HX⋯water, and HX⋯HX hydrogen bonds, halogen bonds, ionic and long‐range X⋯H contacts. Abstract : The most stable HF and HCl forms of the (HX)n (H2 O)n clusters (X = F‐I, n = 2, 3) do not experience dissociation of any of the acid moieties, even with three water molecules. In contrast, in HBr and HI clusters, one of the acid fragments does dissociate. The broad spectrum of contacts in these species includes H2 O⋯H2 O, HX⋯H2 O, and HX⋯HX hydrogen bonds, halogen bonds, ionic and long‐range X⋯H contacts